2012
DOI: 10.1186/1746-1596-7-68
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pathological and oncological outcomes based on extended prostate biopsy results in patients with prostate cancer receiving radical prostatectomy: a single institution study

Abstract: BackgroundThe prediction of pathological outcomes prior to surgery remains a challenging problem for the appropriate surgical indication of prostate cancer. This study was performed to identify preoperative values predictive of pathological and oncological outcomes based on standardized extended prostate biopsies with core histological results diagrammed/mapped in patients receiving radical prostatectomy for prostate cancer clinically diagnosed as localized or locally advanced disease.MethodsIn 124 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The results of our study regarding the prediction of the EPE status in operative specimens were also consistent with those observed in previous studies, in which factors predicting EPE in biopsy specimens were reported as the number of corresponding positive cores, maximum tumor length, maximum cancer-involvement percentage among corresponding cores, and Gleason score (Pound et al 1999;Stamey et al 1999;Quinn et al 2003;Ishizaki et al 2012). In addition, we demonstrated a significant association of these parameters in the preoperative biopsy with the EPE status in the operated prostatectomy specimen for the first time using cancer site prediction methods based on the biopsy procedure with the marking technique.…”
Section: Gls Of Prostatectomysupporting
confidence: 80%
“…The results of our study regarding the prediction of the EPE status in operative specimens were also consistent with those observed in previous studies, in which factors predicting EPE in biopsy specimens were reported as the number of corresponding positive cores, maximum tumor length, maximum cancer-involvement percentage among corresponding cores, and Gleason score (Pound et al 1999;Stamey et al 1999;Quinn et al 2003;Ishizaki et al 2012). In addition, we demonstrated a significant association of these parameters in the preoperative biopsy with the EPE status in the operated prostatectomy specimen for the first time using cancer site prediction methods based on the biopsy procedure with the marking technique.…”
Section: Gls Of Prostatectomysupporting
confidence: 80%
“…He reported percentages of 75.4%, 24.2% and 0.4% for cT1, cT2 and cT3, respectively. Unlike these two studies, which evaluated only low-risk populations, the study of Karavitakis et al found 48% cT1, 36% cT2 and 16% cT3 in a cohort of 95 patients with localized PCa (24).…”
Section: Discussionmentioning
confidence: 85%
“…It is well known the prognosis of prostatic adenocarcinoma depend on its Gleason score, positive surgical margin(PSM), perineural invasion (PNI), and abnormal expression of some genes [21,22]. Nevertheless, these items are not fit with other less happened neoplasms in prostate, such as lymphoma.…”
Section: Resultsmentioning
confidence: 99%